2017
DOI: 10.15406/ghoa.2017.06.00195
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Awareness Levels toward Colorectal Cancer Early Detection and Prevention in Saudi Arabia

Abstract: Background: Awareness of healthy individuals with colorectal cancer (CRC) can identify segments of the population that would most benefit from targeted education programs. Therefore, the aim of the present study was to assess the levels of awareness towards early colonoscopy screening and surgical management of colorectal cancer in the Kingdom of Saudi Arabia (KSA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
5
4
1
Order By: Relevance
“…For instance, only 51.9% of the participants in our study were aware that becoming older may be a risk factor for CRC. A similar percentage was found in both studies by Tfaily et al and Almutlaq et al, where they reported that 48.6% and 48.9% of the participants agreed that age is one of the CRC risk factors [ 19 , 44 ]. Even though younger populations seek more knowledge regarding the benefits of healthy eating than general health, the acquired knowledge sometimes needs to be corrected or added [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For instance, only 51.9% of the participants in our study were aware that becoming older may be a risk factor for CRC. A similar percentage was found in both studies by Tfaily et al and Almutlaq et al, where they reported that 48.6% and 48.9% of the participants agreed that age is one of the CRC risk factors [ 19 , 44 ]. Even though younger populations seek more knowledge regarding the benefits of healthy eating than general health, the acquired knowledge sometimes needs to be corrected or added [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the results of this study showed higher knowledge and awareness levels among participants than those reported in previous studies done in the Middle East, including Jordan [ 19 , 21 , 24 , 43 , 44 ]. For instance, our results contradict the results of both Taha et al and Mhaidat et al, who found that CRC knowledge among Jordanians was either fair or poor [ 21 , 23 ], and contradicted other studies conducted in the Mediterranean Basin [ 19 , 43 ] but were in line with our results in which there is are high knowledge and awareness levels among participants regarding CRC and its risk factors [ 24 ].…”
Section: Discussioncontrasting
confidence: 59%
“…The risk factors of CRC include nonmodifiable risk factors such as aging, gender, prior colon diseases such as inflammatory bowel disease, type 2 diabetes mellitus (DM-2), family history of the CRC, and polyp, [22][23][24][25] and modifiable risk factors such as lack of physical activity, smoking, alcohol drinking, obesity, low fiber diet, high red meat, and low fruit and vegetable intake in the diet. 13,[26][27][28][29] The warning signs and symptoms of CRC are bloody stool, unexplained weight loss, change in bowel habit, anemia, lower abdominal lump, rectal bleeding, and chronic abdominal pain. [30][31][32][33] Nevertheless, increasing the awareness of people about lifestyle modification, predictor identification, and recognizing warning signs and symptoms may be important to reduce CRC morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in the Middle East, it is the most common cancer diagnosed among the male population [1]. In Saudi Arabia, CRC are most often diagnosed at a late stage, which makes it one of the most common cancers among men with poor prognostic outcomes in the country [2].…”
Section: Introductionmentioning
confidence: 99%